Pricing Efficiency of the Vegetable Market in Malaysia - Hashim, Sharifah (1994)

(untitled)
Pricing inefficiency has been blamed as one of the causes for the decline in domestic vegetable production. Structural differences, system of consignment and close price discovery mechanism increase the market power of intermediaries, especially the wholesalers. Hence, changes in the wholesale price are not transmitted to farm level in a similar manner when it increases and decreases. Farm price is more responsive to decreases rather than increases in the wholesale price. Any rise in production cost which does not commensurate with prices received by farmers attract them to switch to more profitable crops or industries which then affects vegetable production. This study provides empirical evidence to prove that asymmetric price transmission occurs in the vegetable market. Such evidence provides proof to the government that wholesalers use their market power to employ pricing strategies which result in complete and rigid pass-through of cost increases but slower and less complete transmission of cost savings to the farmers. This problem requires effective measures in the effort to enhance the development of the vegetable industry in the country. The univariate residual cross-correlation approach by Haugh (1972, 1976) and Pierce (1977) and Granger's test of causality were used to ascertain relationships between market levels in price fonnation. Improved Wolffram's asymmetry procedure with a distributed lag model was adopted and estimated for a subset of fresh vegetables. Time series data on prices consisting of 204 weekly observations were utilized for the purpose. Each series represents the average of five main market centres in the country. The results obtained show that the wholesale market tends to be a major node for pricing. Both retail and farm prices generally lag wholesale price changes. For the eleven most popular vegetables studied, the evidence clearly indicates that price changes are not transmitted throughout the vertical system. Retail prices tend to adjust quickly to increases in wholesale prices. In contrast, farm prices tend to reflect more fully decreases in wholesale price relative to increases. Thus fluctuations in wholesale prices are not beneficial to both parties. Improvements in the marketing system geared toward a more competitive market and open pricing mechanism, supported by improvements in production technology are essential to sustain production of vegetables. Any government development programmes such as setting up auction market ,should be critically planned and implemented with the co-operation of all related agencies. The programmes should also be geared towards effective monitoring, collecting and dissemination of market information among market particl.}jants.